Pengaruh Return on Equity, Ukuran Perusahaan, Quick Ratio, dan Struktur Aktiva Terhadap Struktur Modal: Studi Empiris pada Perusahaan Sub Sektor Automobiles and components yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Mulyani, Sri; Hakim, Astrid Dita Meirina (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to determine the effect of Return on equity, Company Size, Quick ratio, and Asset Structure partially on the Capital Structure in the Automobiles and Component sub-sector listed on the Indonesia Stock Exchange for the 2019–2023 period. The selection of samples in this study uses a purposive sampling method based on certain criteria that are adjusted to the purpose of the research problem, the number of samples used in this study is 9 out of 17 companies in the Automobiles and components sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. This study uses a panel data regression statistical analysis tool assisted by the Eviews version 12 program and Microsoft Excel 2010. The results of this study show that Return On Assets, Company Size, and Asset Structure partially have no effect on capital structure. However, the Quick ratio partially affects the Capital Structure.